Micro and macro geographical analysis of Y-chromosome lineages in South Iberia. (July 2017) - Rey-González, D.; Gelabert-Besada, M.; Cruz, R.; Brisighelli, F.; Lopez-Soto, M.; Rasool, M.; Naseer, M.I.; Sánchez-Diz, P.; Carracedo, A.
Highlights: We describe the impact of the Arab and Berber expansion on the Iberian Peninsula. The Y chromosome variation analysis relies on the study of 27-YSNPs and 17 Y-STRs. The Moorish influence in Andalusia is not stronger than in other Iberian populations. North African influence is not bigger in Iberia than in the rest of Southern Europe. 80% of samples belonging to J-M304 haplogroup display the DYS458*.2 allelic variant. Abstract: In this study, we intend to identify the evolutionary footprints of the South Iberian population focusing on the Berber and Arab influence, which has received little attention in the literature. Analysis of the Y-chromosome variation represents a convenient way to assess the genetic contribution of North African populations to the present-day South Iberian genetic pool and could help to reconstruct other demographic events that could have influenced on that region. A total of 26 Y-SNPs and 17 Y-STRs were genotyped in 144 samples from 26 different districts of South Iberia in order to assess the male genetic composition and the level of substructure of male lineages in this area. To obtain a more comprehensive picture of the genetic structure of the South Iberian region as a whole, our data were compared with published data on neighboring populations. Our analyses allow us to confirm the specific impact of the Arab and Berber expansion and dominion of the Peninsula. Nevertheless, our results suggest that this influence is not bigger in Andalusia than in other Iberian populations.